Neuronal heterogeneity in the ventral tegmental area: Distinct contributions to reward circuitry and motivated behavior - N. Dalton Fitzgerald; Jeremy J. Day (Addiction Neuroscience)
The ventral tegmental area (VTA) is a critical component of brain reward circuitry that influences motivation, learning, and emotional regulation. Although this role was traditionally attributed primarily to VTA dopamine (DA) neurons, recent advances in transcriptomics and intersectional genetics have revealed significant cell type heterogeneity within the VTA, challenging these established notions. Distinct subtypes of DA neurons can be identified across the VTA and substantia nigra pars compacta (SNc) by characteristics that include gene expression patterns (molecular identity), connectivity motifs (network identity), and patterns of task-linked activity and neurotransmitter release (computational identity). This review aims to synthesize current knowledge of diverse neuronal populations in the VTA, including distinct subtypes of DA, glutamate (GLUT), and GABAergic neurons and combinatorial cells alongside well-characterized markers of these neuronal subclasses. Furthermore, this review highlights known projection targets and the role of diverse VTA cell types in motivated behavior. Finally, we highlight emerging intersectional techniques that enable targeted studies of the vast array of cell types and discuss areas of research important for the future direction of the field. Understanding VTA cell type heterogeneity may yield new insights into the reward system, offering potential avenues for treating substance use disorders and other related conditions.